2023
DOI: 10.1002/chem.202202887
|View full text |Cite
|
Sign up to set email alerts
|

Nontoxic Artificial Chloride Channel Formation in Epithelial Cells by Isophthalic Acid‐Based Small Molecules

Abstract: Artificial channels capable of facilitating the transport of Cl À ions across cell membranes while being nontoxic to the cells are rare. Such synthetic ion channels can mimic the functions of membrane transport proteins and, therefore, have the potential to treat channelopathies by replacing defective ion channels. Here we report isophthalic acid-based structurally simple molecules 1 a and 2 a, which self-assemble to render supramolecular nanochannels that allow selective transport of Cl À ions. As evident fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…48 Very recently, isophthalic acid-based artificial ion channels were also developed by us, which were found to be nontoxic to cells even up to 100 mM concentrations. 49 On the other hand, recent findings have revealed that natural products like prodigiosin, tambjamines, and sphingolipidsderived ionophores are capable of inhibiting the growth of several cancer cells. [50][51][52][53][54][55][56][57] Thereafter, several artificial ion transport systems have been investigated for their potential applications in anticancer therapy.…”
Section: Manzoor Ahmadmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Very recently, isophthalic acid-based artificial ion channels were also developed by us, which were found to be nontoxic to cells even up to 100 mM concentrations. 49 On the other hand, recent findings have revealed that natural products like prodigiosin, tambjamines, and sphingolipidsderived ionophores are capable of inhibiting the growth of several cancer cells. [50][51][52][53][54][55][56][57] Thereafter, several artificial ion transport systems have been investigated for their potential applications in anticancer therapy.…”
Section: Manzoor Ahmadmentioning
confidence: 99%
“…Very recently, we introduced artificial channels developed from isophthalic acid-based small organic molecules to transport This journal is © The Royal Society of Chemistry 2023 chloride ions across epithelial cells while being nontoxic even up to a loading concentration of 100 mM. 49 We synthesised 23a-23c and 24a-24c (Fig. 15) with different substituents to fine-tune lipophilicity and membrane permeability.…”
Section: A Nontoxic Ion Transport Systemsmentioning
confidence: 99%